PENGARUH ETIKA PROFESI DAN PROFESIONALISME AUDIT TERHADAP KUALITAS AUDIT (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK DI JAKARTA PERIODE TAHUN 2021) - Eko Supriyanto; Paniran; Nurhaini (The Asia Pacific Journal Of Management Studies, 2023)
Audit quality is the probability that an auditor finds and reports a violation in the auditee's accounting system. As a proxy for audit quality, CPA firm size is often associated with firm reputation. In this case, reputation is related to the client and its resources, both human resources and wealth (assets). So that his reputation has also been noticed by the public and causes them to conduct audits to be more careful. On the other hand, audit fees as a proxy for audit quality will depend on several factors in the audit engagement, namely: the client's finances, the size of the client's firm, the size of the CPA firm, the expertise of the auditor. This study aims to examine and analyze the effect of professional ethics and audit professionalism on audit quality at a public accounting firm in Jakarta in 2021. The method used in this study is a qualitative method with primary data. The sampling technique used a questionnaire based on certain criteria obtained 30 respondents from several public ac counting firms in Jakarta as research samples. The analysis technique uses multiple linear regression with the tools of IBM SPSS Statistic 24.